Do-It-Yourself Astronomy: Getting the best out of a science kit - Rennie, Leonie; Howitt, Christine; Evans, Rosemary; Mayne, Fiona (Australian Science Teachers Association, 2010)
This paper reports an investigation of how four teachers in four different schools used an Astronomy Science Kit. Their varied experiences, along with their varied levels of knowledge and experience in teaching science, considered in the context of other research about science kits, are used to draw conclusions about how best such Do-It-Yourself Science Kits might be prepared and used by teachers in their classrooms.